ANALISIS PERILAKU MASYARAKAT DALAM MEMILIH MEREK HANDPHONE DENGAN MENGGUNAKAN ANALISIS FAKTOR (Studi Kasus Mahasiswa Universitas Udayana) - RANTASARI, SANG AYU PUTRI INDRIA; SUCIPTAWATI, NI LUH PUTU; TASTRAWATI, NI KETUT TARI (E-jurnal matematika, 2015)
The purpose of this study is to determine factors that influence consumer’s decisions to choose a brand of mobile phone and to determine the dominant factor influencing consumer’s decision in choosing brand of mobile phone. The method used is factor analysis. Factor analysis is one part of the analysis of several variables that are used to reduce the data, which is a process to summarize a number of independent variables associated with the factors named mapped or grouped into a new variable. The results showed that there are seven factors that influence consumers to choose the brand of mobile phone: the quality factor, brand, features, product durability, shape or model, price, and warranty. While among the seven factors, the quality factor is a dominant factors that affect consumers to choose brand of mobile phone.